If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 32 + 2y = 2(5y + 8) Reorder the terms: 32 + 2y = 2(8 + 5y) 32 + 2y = (8 * 2 + 5y * 2) 32 + 2y = (16 + 10y) Solving 32 + 2y = 16 + 10y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-10y' to each side of the equation. 32 + 2y + -10y = 16 + 10y + -10y Combine like terms: 2y + -10y = -8y 32 + -8y = 16 + 10y + -10y Combine like terms: 10y + -10y = 0 32 + -8y = 16 + 0 32 + -8y = 16 Add '-32' to each side of the equation. 32 + -32 + -8y = 16 + -32 Combine like terms: 32 + -32 = 0 0 + -8y = 16 + -32 -8y = 16 + -32 Combine like terms: 16 + -32 = -16 -8y = -16 Divide each side by '-8'. y = 2 Simplifying y = 2
| x^4/3-10x^2/3=-9 | | 2(x-2)/3=2(x+4)/9 | | -7/-84 | | 2+3*(4-2)+6/3+2 | | 1050+600+5x=800+400+8x | | -x^2+4=y | | 3d+8=-4-(3-2d) | | a+5/a2-4-a+4/a2-4a+4 | | (37b-4)-9(4b+4)=-3 | | 3/4w=-48 | | Y=-4/3x+2 | | (14+2x)(22+2x)=884 | | 3-4w=-48 | | (22b-7)-7(3b+1)=-2 | | (-60+300x)+x=56 | | 2-3/8n=13 | | 6(y+2)-7=2(y-7) | | (14+2x)(22+2x)=0 | | 3(x+8)=5(x+3)-x | | 1/2(x+4)=5 | | 3(x+8)=5(x+3) | | 308+72x+4x^2=0 | | n-3/8n=13 | | 4.34/567.8 | | 2=x/10 | | -3y+8=2(2y-3) | | X^2+11x+9=9 | | 2.52/0.4 | | -(3/5)x=(6/35) | | 28+x+90=180 | | (2x-3)(x-1)=6+2(x+2)(x+3) | | 3/21,1/15 |